Dynamics of Regional Economic Development of Regencies/Cities in Central Java Province 2018-2020: Dinamika Pembangunan Ekonomi Wilayah Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2018-2020 - Maharani, Dyah Ayu; Hasmarini, Maulidyah Indira (Procedia of Social Sciences and Humanities, 2022)
This study aims to analyze the effect of Poverty Level, Education Level, Per capita Income Level and Open Unemployment Rate on Regional Economic Development to determine the Dynamics of Regional Economic Development in 35 Regencies/Cities in Central Java Province in 2018-2020. this research uses panel data method using eviews8 software. From the results of the study, it can be concluded that partially the variables of the Poverty Level, Education Level, and Open Unemployment Rate have a negative and significant effect on Regional Economic Development, while the Per Capita Income Level variable has no effect on the Regional Economic Development variable. The simultaneous influence of the variables of Poverty Level, Education Level, Per Capita Income Level and Open Unemployment Rate is significant at 83.63% and the remaining 16.37% is influenced by other factors that are not included in the model. This research is expected for the government to pay attention to the things that affect regional economic development in every Regency/City in Central Java Province so that they can be taken into consideration in making economic development plans. areas in every Regency/City in Central Java Province so that.